Constructing knowledge within the photographic apparatus - Närhinen, Tuula; Niemelä-Nyrhinen, Jenni; Leisti, Tuomas (Taylor & Francis, 2025)
This article brings together three disciplines with different scholarly, methodological and theoretical views on photography: media studies, visual art and perceptual psychology. Our multidisciplinary approach focuses on the operations of the photographic apparatus, an umbrella concept that allows us to examine the construction of knowledge within a wide range of practices, technologies and discourses. Following Hans Belting’s anthropological iconology, we propose that while examining photographic images, it is also important to recognise their non-iconic determinants — namely, the workings of the medium and the bodies implicated. The common denominator to our joint endeavour is the disposition of procedural knowledge constructed within the social, technological and psychological processes of photographic mediation. We argue that recognising the connective function of images as links between the sensory and ideational modes of knowing is paramount to acknowledging the epistemic implications of photographic images in current visual cultures.
Keywords: photographic art; taiteellinen tutkimus; artistic research; valokuvataide; monitieteisyys; multidisciplinary research